2012
DOI: 10.1186/2110-5820-2-43
|View full text |Cite
|
Sign up to set email alerts
|

A fresh look at paralytics in the critically ill: real promise and real concern

Abstract: Neuromuscular blocking agents (NMBAs), or “paralytics,” often are deployed in the sickest patients in the intensive care unit (ICU) when usual care fails. Despite the publication of guidelines on the use of NMBAs in the ICU in 2002, clinicians have needed more direction to determine which patients would benefit from NMBAs and which patients would be harmed. Recently, new evidence has shown that paralytics hold more promise when used in carefully selected lung injury patients for brief periods of time. When use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
(89 reference statements)
1
17
1
1
Order By: Relevance
“…[57][58][59][60] Of note, these studies have evaluated cisatricurium, while aminosteroids (ie, rocuronium, vecuronium) have been found to have a higher risk of myopathy and neuropathy and potentially deserve separate investigation. 61 To date, no RCTs have evaluated the utility of NMB in children with PARDS. A prospective physiologic study by Wilsterman et al showed improved OI in pediatric patients with acute hypoxemic respiratory failure who received continuous NMB during mechanical ventilation.…”
Section: Recruitment Maneuversmentioning
confidence: 99%
“…[57][58][59][60] Of note, these studies have evaluated cisatricurium, while aminosteroids (ie, rocuronium, vecuronium) have been found to have a higher risk of myopathy and neuropathy and potentially deserve separate investigation. 61 To date, no RCTs have evaluated the utility of NMB in children with PARDS. A prospective physiologic study by Wilsterman et al showed improved OI in pediatric patients with acute hypoxemic respiratory failure who received continuous NMB during mechanical ventilation.…”
Section: Recruitment Maneuversmentioning
confidence: 99%
“…In addition, cisatracurium metabolism does not depend on renal or hepatic functionwhich may increase its use in patients with multiorgan dysfunction and an increased risk of death. In addition, the chemical structure of cisatracurium may reduce the risk of ICU-associated weakness when compared with other neuromuscular blockade agents (10). Consequently, other neuromuscular blockade agents may not have the same potential beneficial effects on patient outcomes.…”
mentioning
confidence: 99%
“…The most used NMBAs in patients with ARDS is cisatracurium. Comparison with cisatracurium, vecuronium has different pharmacological properties [24]. Lyu [20] evaluated the effects of vecuronium in patients with moderate or severe ARDS and they found vecuronium is associated with better prognosis.…”
Section: Discussionmentioning
confidence: 99%